Hepatocellular carcinoma surveillance, early detection and survival in a privately insured US cohort. (26th January 2020) - Chen, Vincent L.; Singal, Amit G.; Tapper, Elliot B.; Parikh, Neehar D.
Abstract: Background/Aims: Semiannual hepatocellular carcinoma (HCC) surveillance is recommended in patients with cirrhosis; however, recent studies have raised questions over its utility. We investigated the impact of surveillance on early detection and survival in a nationally representative database. Methods: We included patients with cirrhosis and HCC from the Optum database (2001‐2015) with >6 months of follow‐up between cirrhosis and HCC diagnoses. Surveillance adherence was defined as proportion of time covered (PTC), with each 6‐month period after abdominal imaging defined as 'covered'. To determine the association between surveillance and mortality, we compared PTC between fatal and non‐fatal HCC. Results: Of 1001 patients with cirrhosis and HCC, 256 died with median follow‐up 30 months. Median PTC by any imaging was greater in early‐stage vs late‐stage HCC (43.6% vs 37.4%, P  = .003) and non‐fatal vs fatal HCC (40.8% vs 34.3%, P  = .001). In multivariable analyses, each 10% increase in PTC was associated with increased early HCC detection (OR 1.07, 95% CI 1.01‐1.12) and decreased mortality (HR 0.95; 95% CI 0.90‐1.00). On subgroup analysis, PTC by CT/MRI was associated with early tumour detection and decreased mortality; however, PTC by ultrasound was only associated with early detection but not decreased mortality. These findings were robust across sensitivity analyses. Conclusions: In a US cohort of privately insured HCC patients, PTC by any imaging modality was associated with increased early detection and decreased mortality. Continued evaluation of HCC surveillance strategies and effectiveness is warranted.